POSSIBILITIES AND PRACTICAL MECHANISMS OF COLLABORATIVE PEDAGOGY IN IMPROVING THE QUALITY OF EDUCATION - Karimjon Shavkat o‘g‘li Ne’matov (International Journal of Literature and Language Studies, 2026)
This article examines the possibilities and practical mechanisms of collaborative pedagogy in improving the quality of education. It highlights the advantages of an educational approach based on cooperation among teachers, students, and peers. Collaborative pedagogy is shown to enhance student motivation, account for individual differences, foster critical thinking and creativity, and create an inclusive learning environment. The article demonstrates that the widespread implementation of this approach in Uzbekistan can significantly improve not only academic achievements but also students’ socio-emotional competencies.